Identification of major environmental factors driving phytoplankton community succession before and after the regime shift of Erhai Lake, China. (February 2023) - Yang, Ruibo; Fan, Xian; Zhao, Lei; Yang, Kun
Highlights: Long time-series monitoring data covering the period of regime shift were collected. The regime shift was revealed from biological indicators and hydrochemical parameters. Before the regime shift, nutrients exhibited a significant limiting effect on algae. After the regime shift, light became the key factor driving algal community succession. Abstract: In lake ecosystems, regime shifts can induce changes in physical and biological components, particularly phytoplankton community structure, as well as across multiple trophic levels. Phytoplankton community succession may be driven by different environmental factors before and after regime shift; however, owing to the abruptness of the regime shift, long-term observations encompassing both periods are scarce, limiting our ability to identify the shift of key drivers of phytoplankton community succession. Here, an analysis was conducted based on long-term observations (involving phytoplankton community and environmental variables from 1997 to 2008) in Erhai Lake, a eutrophic lake in China that may have undergone a regime shift in 2001–2003. The dynamics of hydrochemical parameters and phytoplankton community composition indicated a distinct regime shift between 2001 and 2003. The phytoplankton community evolved over a decadal period toward community structure simplification, dominance of individual species, and homogenization of species composition. Prior to the regime shift (1997–2000), the eutrophic status of Erhai Lake was oligotrophic, and the phytoplankton community was characterized by high biodiversity and low biomass, with Cyanophyta, Bacillariophyta, and Cryptophyta being the dominant species. Nutrient concentrations had a significant limiting effect on phytoplankton, with total nitrogen concentration being the primary limiting factor. Following the regime shift (2005–2008), the phytoplankton community exhibited low biodiversity and high biomass, with the dominant taxa shifting to Cyanophyta, Chlorophyta, and Bacillariophyta. Light became the primary driver of phytoplankton community succession. Our study was based on long-term observations covering regime shifts in Erhai Lake, providing strong evidence that the phytoplankton community is influenced by nutrients in oligotrophic status. However, as nutrient concentrations increase, especially once the threshold is exceeded, species interactions may shift from competition for nutrients to competition for light. This implies that the resource competition theory, which integrates nutrient- and light-based approaches, provides an effective approach to predicting phytoplankton community succession, and that measures to improve underwater light environments should be considered as an additional option for nutrient load reduction in eutrophic lakes.